Plate and frame type membrane for treating printing and dyeing wastewater and preparation method of plate and frame type membrane
By applying a self-healing hydrophilic coating on the surface of the polyethersulfone-based membrane of the plate-frame ultrafiltration membrane, the problems of flux reduction and membrane failure in traditional membranes under high concentration pollution environments are solved, and higher anti-pollution ability and service life are achieved.
Patent Information
- Application Number
- CN202510193621.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-21
- Publication Date
- 2025-03-25
- Estimated Expiration
- Not applicable · inactive patent
AI Technical Summary
When traditional plate-frame ultrafiltration membranes treat high-concentration pollutants or high-viscosity fluids, it is easy for the membrane surface to form a contaminated layer that is difficult to clean, resulting in reduced flux and membrane failure.
A polyethersulfone-based film is used and a self-healing hydrophilic coating is coated on its surface. The coating consists of polyvinyl alcohol, polyurethane elastomer, temperature-sensitive polymer, nanomaterial and solvent-modifying solvent. The hydrophilicity and pollution resistance of the coating are enhanced by solvation modification and surface functionalization treatment.
It significantly improves the surface hydrophilicity of the film, weakens the adhesion between pollutants and the film surface, delays the formation of contaminated layers and the failure of the film, and improves the film's anti-pollution ability and service life.
Smart Images

Figure SMS_1 
Figure SMS_3 
Figure SMS_4
Abstract
Description
Technical Field
[0001] The invention relates to a plate-frame membrane for treating printing and dyeing wastewater and a preparation method thereof, belonging to the technical field of sewage treatment. Background Art
[0002] Plate and frame ultrafiltration membranes are widely used in wastewater treatment, especially in the treatment of printing and dyeing wastewater. It separates suspended matter, colloidal substances and macromolecular organic matter in water through physical filtration. Plate and frame ultrafiltration membranes are usually composed of multiple ultrafiltration membranes arranged in a frame. The membranes screen out pollutants in the water through differences in pore size. For the treatment of printing and dyeing wastewater, ultrafiltration membranes can effectively remove dyes, particulate matter and other organic matter in water. However, this membrane technology still faces some technical difficulties in actual application, especially when dealing with high-concentration pollutants or high-viscosity fluids.
[0003] In the treatment of printing and dyeing wastewater, there are many kinds of pollutants in the water, including organic matter, grease, dyes, surfactants and salts. High concentrations of organic pollutants and grease will pollute the surface of the membrane, especially the surface of the membrane will form a contamination layer that is difficult to clean. This contamination not only reduces the flux of the membrane, but also accelerates the failure of the membrane. During use, due to the poor hydrophilicity of the membrane surface, the water molecules have poor contact with the membrane, which leads to enhanced interaction between the membrane surface and pollutants, thereby accelerating the accumulation of pollution and the pollution rate of the membrane. The pores of the membrane are blocked by pollutants, the filtration performance is significantly reduced, and even the membrane flux will drop significantly, which increases the difficulty of maintenance and cleaning.
[0004] Traditional plate-and-frame ultrafiltration membrane technology cannot effectively cope with these challenges. Therefore, improving the membrane's anti-pollution ability and extending the membrane's service life have become technical issues that need to be solved urgently. To this end, solving the membrane surface pollution problem and improving the membrane's performance and stability have become the focus of research. On the basis of existing technologies, developing new technical means to improve the membrane's anti-pollution ability and reduce the accumulation of membrane pollution is one of the future development directions. Summary of the invention
[0005] In view of the shortcomings of the prior art, the object of the present invention is to provide a plate-and-frame membrane for treating printing and dyeing wastewater and a preparation method thereof.
[0006] The above object of the present invention is achieved through the following technical solutions: A plate-and-frame membrane for treating printing and dyeing wastewater comprises a base membrane and a self-repairing hydrophilic coating coated on the surface of the base membrane, wherein: The base membrane is a polyethersulfone ultrafiltration membrane, which is made of polyethersulfone polymer material; The self-repairing hydrophilic coating is prepared by comprising the following components in parts by weight: 60-80 parts of polyvinyl alcohol; 100-120 parts of polyurethane elastomer; 5 to 10 parts of a thermosensitive polymer; 2-5 parts of nanomaterials; 20 to 70 parts of solvent for solvation modification; Wherein, the temperature-sensitive polymer is selected from one of poly (N-isopropylacrylamide) or poly (vinyl alcohol)-poly (N-isopropylacrylamide) copolymer; The nano material is selected from one of nano titanium dioxide or graphene oxide; The solvent for solvation modification is selected from one or more of alcohol solvents, ketone solvents or ether solvents; The solvation modification conditions are a temperature of 150° C. to 250° C. and a pressure of 0.5 MPa to 2 MPa.
[0007] Printing and dyeing wastewater often contains a large amount of organic pollutants, dyes and high-viscosity oils and fats. These pollutants can easily form a pollution layer on the surface of traditional ultrafiltration membranes, resulting in a significant decrease in membrane flux. By coating a self-repairing hydrophilic coating on the surface of a polyethersulfone-based membrane, the present invention significantly improves the surface hydrophilicity of the membrane, thereby weakening the adhesion of pollutants to the membrane surface and reducing the speed and degree of pollutant accumulation. The polyvinyl alcohol and thermosensitive polymer contained in the self-repairing coating further reduce the adhesion of oils and organic matter to the membrane surface through their good hydrophilic properties, so that the membrane can still maintain a high filtration efficiency under high-concentration pollution environments. Polyvinyl alcohol, with its excellent hydrophilic properties, can form a uniform hydrophilic layer on the membrane surface. The hydrophilic layer prevents the adhesion and accumulation of pollutants by reducing the interaction between the membrane surface and hydrophobic pollutants (such as organic matter and oils). The enhanced hydrophilicity makes it easier for water molecules to form a stable hydration film on the membrane surface. This hydration film has a natural anti-pollution barrier effect and can effectively inhibit the adsorption of dye molecules and other organic pollutants in printing and dyeing wastewater. The dynamic response characteristics of thermosensitive polymers (such as poly (N-isopropylacrylamide)) are another key factor in improving the anti-fouling performance of coatings. Such polymers can undergo reversible conformational changes when the temperature changes. For example, within a specific temperature range, the polymer chain segments will show a controllable transition between hydrophobicity and hydrophilicity. This property enables it to release adsorbed pollutants through stimulation (such as temperature increase) when pollutants accumulate on the membrane surface, thereby reducing the formation of a fouling layer. This dynamic response mechanism significantly reduces the stability of surface pollutants, thereby improving the self-cleaning ability of the membrane.
[0008] The synergistic effect of polyvinyl alcohol and thermosensitive polymer in the coating further enhances the anti-pollution effect. In the initial stage, polyvinyl alcohol provides a stable hydrophilic barrier on the membrane surface, significantly reducing the initial adsorption of pollutants; in the pollution accumulation stage, when some pollutants are inevitably adsorbed on the membrane surface, the dynamic responsiveness of the thermosensitive polymer plays a role, inducing conformational changes through temperature stimulation, reducing the interaction force between pollutants and the membrane surface, and promoting the desorption of pollutants. In the long-term operation stage, the combination of thermosensitive polymer and polyvinyl alcohol ensures that the surface state of the membrane is always in dynamic equilibrium, with both the continuous hydrophilic effect of polyvinyl alcohol and the periodic self-cleaning function of thermosensitive polymer, delaying the formation of the pollution layer. At the same time, the nanomaterials in the coating (such as nano titanium dioxide or graphene oxide) further enhance the synergistic effect. Its catalytic and adsorption properties can decompose the complex organic matter adsorbed on the coating, providing a cleaner surface environment for polyvinyl alcohol and thermosensitive polymer, thereby significantly improving the overall anti-pollution ability.
[0009] In addition, traditional plate-and-frame ultrafiltration membranes need to be frequently cleaned or replaced after pollutants accumulate, which increases operating costs and downtime. The introduction of self-healing hydrophilic coatings not only effectively alleviates surface contamination, but also enables self-cleaning of contamination through the dynamic structural characteristics of thermosensitive polymers. When the coating is slightly damaged, the intelligent response behavior of the thermosensitive polymer can repair the functional defects on the coating surface, thereby extending the service life of the membrane. This feature significantly reduces the maintenance frequency of the equipment and improves the stability and operating efficiency of the overall system.
[0010] The present invention enhances the photocatalytic activity and anti-pollution ability of the membrane surface by optimizing the proportion of nanomaterials in the coating components, such as nano titanium dioxide or graphene oxide. These nanomaterials can decompose attached organic matter and dye molecules under ultraviolet irradiation, thereby further improving the anti-pollution ability of the membrane. At the same time, the solvent modification treatment in the coating makes the coating and the base membrane more closely combined, avoids the problem of coating shedding, makes the flux of the membrane more stable, and maintains excellent performance during long-term operation.
[0011] Through the solvation modification process, the present invention prepares a self-repairing coating under the conditions of 150°C to 250°C and 0.5MPa to 2MPa. This process condition not only ensures the uniformity and stability of the coating, but also avoids damage to the base film caused by excessively high temperatures, ensuring the balance of the overall performance of the film. This optimized process improves the manufacturing accuracy of the film and ensures the consistency and practicality of the product.
[0012] Furthermore, the functionalized nanomaterial is nano titanium dioxide with surface functionalization treatment, and the surface functionalization treatment steps are as follows: Step 1: Dissolve nano-titanium dioxide powder in anhydrous ethanol, ultrasonically vibrate to remove impurities, and wash with deionized water until the pH value is close to neutral; Step 2: Dry the washed nano titanium dioxide at 60-80°C for 12 hours; Step 3: Mixing anhydrous ethanol, deionized water and aminotrichlorosilane to obtain a reaction solution, wherein the mass of the aminotrichlorosilane is 1 / 10 of the nano titanium dioxide powder; Step 4: adding the dried nano titanium dioxide to the reaction solution, stirring and reacting at 25° C. for 2 to 6 hours to form functionalized nano titanium dioxide; Step 5: Wash the reaction product by centrifugation or filtration, and repeatedly wash with anhydrous ethanol and deionized water to remove unreacted reagents and by-products; Step 6: Dry the cleaned nano-titanium dioxide at 60° C. for 12 hours to obtain surface functionalized nano-titanium dioxide.
[0013] Surface functionalization treatment significantly improves the photocatalytic performance of nano-titanium dioxide. In the treatment of printing and dyeing wastewater, dye molecules and organic pollutants often have complex chemical structures, and traditional membrane materials are difficult to effectively decompose these pollutants. Through functionalization treatment, the active surface area of nano-titanium dioxide is significantly increased, and the amino groups on its surface can promote the adsorption and capture of pollutants, so that more pollutant molecules are guided to the photocatalytic reaction area. In addition, surface functionalization enhances the electron transfer ability of titanium dioxide, and can produce highly active free radicals more quickly under ultraviolet irradiation. These free radicals can effectively decompose dye molecules and organic compounds in wastewater, greatly improving treatment efficiency.
[0014] Nano-titanium dioxide that has not been functionalized is prone to agglomeration in solvents, resulting in poor dispersibility and difficulty in evenly coating the membrane surface. After surface functionalization, stable amino groups are formed on the surface of titanium dioxide nanoparticles. This modified structure can significantly enhance the electrostatic repulsion between particles and avoid particle agglomeration. Better dispersibility makes the coating preparation more uniform, and the coating is more tightly bonded to the base film, which helps to improve the long-term stability of the coating and avoid shedding or peeling during use.
[0015] The surface of functionalized nano-titanium dioxide has highly polar amino functional groups, which can form hydrogen bonds with water molecules, thereby significantly enhancing the hydrophilicity of the coating. The strong hydrophilicity allows the membrane surface to quickly form a hydration layer, which acts as a natural barrier to effectively prevent hydrophobic pollutants (such as dyes and oils) from directly contacting the membrane surface, thereby reducing the probability of pollutant adsorption and delaying the formation of the pollution layer. This feature allows the membrane to maintain a high flux and operating efficiency even in a high-concentration pollution environment.
[0016] Surface functionalization treatment firmly binds aminotrichlorosilane to the surface of nano-titanium dioxide through chemical reaction, which significantly enhances the chemical stability of the modified nano-material to the external environment. In the process of printing and dyeing wastewater treatment, the wastewater may contain a variety of chemical components, such as acids, alkalis, oxidants, etc. These components have potential destructive effects on unmodified titanium dioxide. After functionalization treatment, a stable organic silicon chemical bond structure is formed on the surface of titanium dioxide, which greatly improves its tolerance in complex chemical environments, thereby extending the service life of the coating and reducing the frequency of maintenance and replacement.
[0017] Furthermore, it also comprises 1 to 3 parts by weight of a conductive polymer material, wherein the conductive polymer material is selected from polyaniline or polypyrrole.
[0018] Conductive polymer materials usually have good flexibility and mechanical strength, and can form a uniform composite structure with polyvinyl alcohol and thermosensitive polymers in the coating. Its network structure can disperse external stress and reduce the risk of the coating falling off due to shear force or wear in the use environment. Materials such as polyaniline and polypyrrole have good conductivity and can form electron channels inside the coating. This property helps to efficiently transfer electrons during the photocatalytic reaction, and combined with the catalytic activity of nano-titanium dioxide, further improves the degradation efficiency of organic pollutants.
[0019] Polyaniline and polypyrrole molecular chains contain polar groups such as amino and hydroxyl groups, which can form hydrogen bonds with water molecules to increase the hydrophilicity of the membrane surface. The enhanced hydrophilicity makes the formation of the hydrated membrane more stable, thereby further reducing the possibility of pollutants adhering to the membrane surface. The conductive polymer material and polyvinyl alcohol work together to further consolidate the stability of the hydrophilic layer, allowing the membrane to maintain high flux and low pollution performance even in complex wastewater environments.
[0020] The dye molecules in printing and dyeing wastewater usually have a complex charge distribution. Conductive polymer materials can adsorb or repel dye molecules through electrostatic interactions under electrical stimulation, thereby enhancing the separation effect. The active oxygen and free radicals produced by the electrochemical reaction on the membrane surface can directly degrade the organic molecules in the wastewater, thereby reducing the burden on subsequent treatment units. Conductive polymer materials can induce electrochemical reactions under low voltage to produce active oxygen or free radicals. These active substances can effectively oxidize and decompose organic pollutants and dye molecules attached to the membrane surface, reducing the formation rate of the pollution layer. By periodically applying electrical stimulation, the conductive polymer material can change its surface charge density, thereby weakening the adhesion of pollutants to the membrane surface and promoting the desorption of adsorbed pollutants. Compared with traditional passive anti-pollution membranes, this active anti-pollution mechanism significantly improves the long-term operation stability of the membrane.
[0021] Furthermore, it also includes 0.5 to 2 parts by weight of metal nanoparticles, wherein the metal nanoparticles are nanosilver.
[0022] Nanosilver particles release silver ions, destroy the bacterial cell membrane structure and interfere with its metabolic process, thereby effectively inhibiting the growth and reproduction of bacteria. The high temperature and high concentration of organic matter in printing and dyeing wastewater provide a suitable growth environment for microorganisms, which easily form a biofouling layer on the surface of traditional membranes. The introduction of nanosilver particles can effectively inhibit this process, prevent microbial attachment and reduce the decrease in membrane flux caused by biofouling.
[0023] The combination of nanosilver with conductive polymer materials and nano-titanium dioxide in the coating forms multiple anti-pollution mechanisms. On the one hand, nanosilver particles can inhibit microbial contamination. On the other hand, they synergistically enhance the photocatalytic degradation ability of the membrane with nano-titanium dioxide, further reducing organic pollution and the accumulation of dye molecules on the membrane surface. Nanosilver particles have a unique surface plasmon resonance effect, which can improve the absorption efficiency of light energy and promote the separation of electron-hole pairs. This effect enhances the photocatalytic activity of nano-titanium dioxide, enabling it to more efficiently produce active oxygen under ultraviolet irradiation and decompose complex organic pollutants and dye molecules in printing and dyeing wastewater.
[0024] Furthermore, the base film has a thickness of 100 to 200 microns.
[0025] The thickness of the base membrane ensures a balance between membrane strength and filtration efficiency. The thickness range of 50 to 200 microns enables the base membrane to withstand mechanical stress under high pressure conditions while also having good water permeability and filtration performance. Moderate membrane thickness can also reduce fluid resistance and improve wastewater treatment efficiency. In addition, a thinner base membrane reduces manufacturing costs, making this plate-and-frame membrane more competitive in the market.
[0026] Furthermore, the thickness of the self-repairing hydrophilic coating is 10 to 15 microns.
[0027] The coating thickness is set at 10 to 15 microns, a range that ensures the effective performance of the coating function while avoiding the problem of reduced water permeability caused by excessive coating thickness. The moderate coating thickness not only enhances the self-healing ability of the coating, but also ensures its uniformity and bonding with the base membrane, thereby optimizing the overall performance of the membrane. The thin and uniform coating also increases the flow rate and efficiency of wastewater treatment, further improving the practicality of the membrane.
[0028] Furthermore, the alcohol solvent used in the solvation modification is one of methanol, ethanol, and isopropanol, the ketone solvent is one of acetone and dimethyl ketone, and the ether solvent is one of dimethyl ether and tetrahydrofuran.
[0029] The effect of solvation modification is ensured by specifying the solvent types in detail. The selection of alcohol, ketone and ether solvents provides good solubility and dispersibility for the coating material, ensuring the uniformity of the coating. The specific solvent types and proportions effectively optimize the physical and chemical properties of the coating while avoiding environmental pollution and unnecessary material waste. The solvation modification treatment conditions further enhance the bonding between the coating and the base film, making the coating more stable under the high temperature and high pressure environment of wastewater treatment.
[0030] Furthermore, the amount of hydrophilic functional groups introduced into the coating is 0.5 to 2 mmol / g.
[0031] The amount of hydrophilic functional groups introduced is controlled at 0.5-2mmol / g, so that the coating can form a uniform hydrophilic barrier on the membrane surface. This barrier can quickly adsorb water molecules and form a hydration layer on the membrane surface. As a natural barrier, the hydration layer effectively reduces the direct contact between hydrophobic pollutants (such as dye molecules, organic matter and oily substances) and the membrane surface, thereby reducing the adhesion and accumulation of pollutants. When the introduction amount is 0.5-2mmol / g, the number of hydrophilic functional groups (such as hydroxyl, carboxyl or amino) is sufficient to cover the membrane surface, while avoiding the problem of structural instability or mutual shielding between hydrophilic functional groups that may be caused by excessive introduction. If the introduction amount of hydrophilic functional groups is less than 0.5mmol / g, the hydrophilicity of the coating surface may be insufficient, resulting in difficulty in forming a hydration membrane, thereby reducing the membrane's anti-pollution ability and flux performance. When the introduction amount exceeds 2mmol / g, accumulation or mutual shielding may occur between functional groups, resulting in a decrease in the hydrophilic effect. At the same time, too high a functional group density may affect the mechanical properties of the coating or the long-term stability of the membrane. By controlling the introduction amount within the range of 0.5 to 2 mmol / g, the present invention achieves a good balance between performance and stability.
[0032] A method for preparing a plate-and-frame membrane for treating printing and dyeing wastewater comprises the following steps: S1: preparing a base membrane, wherein the base membrane is a polyethersulfone ultrafiltration membrane made of a polyethersulfone polymer material; S2: preparing a self-healing hydrophilic coating, mixing polyvinyl alcohol, polyurethane elastomer, thermosensitive polymer and solvent for solvation modification, and then adding nanomaterials; Wherein, the temperature-sensitive polymer is selected from poly (N-isopropylacrylamide) or poly (vinyl alcohol)-poly (N-isopropylacrylamide) copolymer, and the nanomaterial is selected from nano titanium dioxide or graphene oxide; S3: performing a solvation modification treatment, the specific method being: performing a solvation modification under the conditions of a temperature of 150° C. to 250° C. and a pressure of 0.5 MPa to 2 MPa; S4: coating the self-healing hydrophilic coating on the surface of the base film, ensuring that the coating is uniform and free of bubbles; S5: The coating is solidified by drying or hot pressing to obtain a plate-and-frame membrane for treating printing and dyeing wastewater.
[0033] By adopting the above technical solution, the functions of the base film and the coating can be fully exerted. The reasonable design of each step optimizes the structure and function of the base film and the coating. During the preparation of the coating, the uniformity and performance stability of the coating are ensured by solvent modification and uniform coating process. The drying or hot pressing curing step further enhances the bonding force between the coating and the base film, so that the final product shows excellent performance in the treatment of printing and dyeing wastewater.
[0034] Furthermore, in the solvation modification process of step S3, the alcohol solvent used is one of methanol, ethanol or isopropanol, the ketone solvent used is one of acetone or dimethyl ketone, and the ether solvent used is one of dimethyl ether or tetrahydrofuran.
[0035] By further refining the specific conditions of the solvent modification step, the controllability and repeatability of the coating preparation process are enhanced. The optimized solvent type and ratio maximize the uniformity and functionality of the coating, ensuring the quality and performance consistency of the final product. At the same time, these refined conditions make the process more environmentally friendly and reduce manufacturing costs.
[0036] Compared with the prior art, the beneficial effects of the present invention are mainly reflected in the following aspects: The present invention provides a plate-and-frame membrane for treating printing and dyeing wastewater and a preparation method thereof. By combining a polyethersulfone-based membrane, a self-healing hydrophilic coating, a multifunctional nanomaterial, a conductive polymer material and an optimized solvation modification process, the membrane performance is comprehensively improved. The polyvinyl alcohol, thermosensitive polymer and nanomaterial in the coating work synergistically to form a stable hydrophilic barrier on the membrane surface, effectively reducing the adhesion of hydrophobic pollutants (such as dyes, organic matter and grease) to the membrane surface, and significantly delaying the formation of a pollution layer; the thermosensitive polymer achieves pollutant desorption through dynamic response characteristics, and the self-cleaning effect is significantly improved, reducing the need for cleaning and extending the operating cycle of the membrane. Surface-functionalized nano-titanium dioxide and conductive polymer materials (such as polyaniline or polypyrrole) decompose complex organic pollutants in wastewater through photocatalytic degradation and electrochemical action, further enhancing the anti-pollution ability.
[0037] The amount of hydrophilic functional groups introduced into the coating (0.5-2 mmol / g) enhances the stability of the hydration layer, making it easier for water molecules to pass through the membrane surface, maintaining a high water flux while preventing pollutant adsorption; the optimization of the base membrane thickness (50-200 microns) improves the mechanical strength while ensuring a good pore structure, providing strong support for efficient separation. The coating thickness (10-15 microns) ensures the stability and durability of the coating in long-term operation, and it is not easy to fall off due to wear or external force, while maintaining good flexibility and mechanical strength. The combination of nanomaterials and conductive polymer materials enhances the photocatalytic activity and chemical stability of the coating, allowing the membrane to maintain long-term performance in complex wastewater environments.
[0038] The alcohol, ketone and ether solvents (such as methanol, ethanol, acetone, tetrahydrofuran) selected in the solvation modification treatment effectively promote the uniform distribution of the coating and enhance the bonding strength between the coating and the base film under the conditions of temperature 150℃~250℃ and pressure 0.5MPa~2MPa; the drying or hot pressing process further improves the adhesion and functional stability of the coating, while laying the foundation for large-scale industrial production. The anti-pollution performance of the self-healing coating reduces the frequency of cleaning and the use of chemical cleaning agents, prolongs the service life of the membrane, and reduces operating costs. The photocatalytic degradation ability of nano-titanium dioxide further reduces the content of organic pollutants in wastewater, providing support for green and environmentally friendly wastewater treatment.
[0039] The plate-and-frame membrane designed by the present invention can efficiently treat printing and dyeing wastewater, and is also suitable for other wastewater treatment scenarios containing high concentrations of organic pollutants, grease or dyes. The modular design of the membrane facilitates integration with existing wastewater treatment systems and has good industrial adaptability and promotion value. Through multi-level technological innovation, the present invention excels in separation efficiency, anti-pollution ability, intelligent response and economy, providing an efficient, environmentally friendly and economical solution for wastewater treatment in highly polluting industries, while opening up a new path for the further development and application of membrane separation technology. DETAILED DESCRIPTION
[0040] The present invention is described in detail below in conjunction with embodiments.
[0041] Example 1 Raw materials and equipment Basement membrane: Polyethersulfone ultrafiltration membrane (manufacturer: Pall Corporation, USA, model: UE010MF).
[0042] Self-healing hydrophilic coating raw materials: Polyvinyl alcohol (manufacturer: Kuraray, model: PVA-224, alcoholysis degree 87%-89%, molecular weight 88,000-98,000); Polyurethane elastomer (manufacturer: Bayer, model: Desmopan® TPU 9370A); Thermosensitive polymer (poly (N-isopropylacrylamide), manufacturer: Sigma-Aldrich, model: P4257); Nanomaterials (nano titanium dioxide, manufacturer: Evonik, Germany, model: P25); Solvent for solvation modification (isopropanol, manufacturer: Shanghai McLean Biochemical Technology Co., Ltd., model: AR grade)
[0043] Equipment: Plate and frame membrane preparation machine, film coating machine, vacuum drying oven, high pressure reactor.
[0044] Preparation steps S1: Preparation of base membrane: Directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, with a base membrane thickness of 150 μm, for subsequent coating process.
[0045] S2: Preparation of self-healing hydrophilic coating: Add polyvinyl alcohol (70 parts) and polyurethane elastomer (110 parts) into isopropanol (50 parts), stir evenly to form a mixed solution; Thermosensitive polymer (8 parts) and nano-titanium dioxide (3 parts) were added to the mixed solution, and stirring was continued for 2 hours to obtain a uniformly dispersed coating precursor solution.
[0046] S3: Solvation modification treatment: The coating precursor liquid was placed in a high-pressure reactor and subjected to a solvent modification treatment at 200° C. and 1 MPa for 3 hours to prepare a coating material with excellent hydrophilicity.
[0047] S4: coating process: Use a coating machine to evenly coat the prepared self-healing hydrophilic coating on the surface of the base film to ensure that there are no bubbles and coating defects; the coating thickness is controlled to be 12 microns.
[0048] S5: Curing process: The coated film was placed in a vacuum drying oven and dried at 80° C. for 6 hours to completely cure the coating to obtain the final plate-and-frame film.
[0049] Example 2 Raw materials and equipment Basement membrane: Polyethersulfone ultrafiltration membrane (manufacturer: Pall Corporation, USA, model: UE010MF).
[0050] Self-healing hydrophilic coating raw materials: Polyvinyl alcohol (manufacturer: Kuraray, model: PVA-224, alcoholysis degree 87%-89%, molecular weight 88,000-98,000); Polyurethane elastomer (manufacturer: Bayer, model: Desmopan® TPU 9370A); Thermosensitive polymer (poly (N-isopropylacrylamide), manufacturer: Sigma-Aldrich, model: P4257); Nanomaterials (nano titanium dioxide, manufacturer: Evonik, Germany, model: P25); Solvent for solvation modification (isopropanol, manufacturer: Shanghai McLean Biochemical Technology Co., Ltd., model: AR grade)
[0051] Equipment: Plate and frame membrane preparation machine, film coating machine, vacuum drying oven, high pressure reactor.
[0052] Preparation steps S1: Preparation of base membrane: Directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, with a base membrane thickness of 100 microns, for subsequent coating process.
[0053] S2: Preparation of self-healing hydrophilic coating: Add polyvinyl alcohol (60 parts) and polyurethane elastomer (100 parts) into isopropanol (20 parts), stir evenly to form a mixed solution; Thermosensitive polymer (5 parts) and nano-titanium dioxide (2 parts) were added to the mixed solution, and stirring was continued for 2 hours to obtain a uniformly dispersed coating precursor solution.
[0054] S3: Solvation modification treatment: The coating precursor liquid was placed in a high-pressure reactor and subjected to a solvent modification treatment at 150° C. and 0.5 MPa for 4 hours to prepare a coating material with excellent hydrophilicity.
[0055] S4: coating process: Use a coating machine to evenly coat the prepared self-healing hydrophilic coating on the surface of the base film to ensure that there are no bubbles and coating defects; the coating thickness is controlled to be 10 microns.
[0056] S5: Curing process: The coated film was placed in a vacuum drying oven and dried at 80° C. for 6 hours to completely cure the coating to obtain the final plate-and-frame film.
[0057] Example 3 Raw materials and equipment Basement membrane: Polyethersulfone ultrafiltration membrane (manufacturer: Pall Corporation, USA, model: UE010MF).
[0058] Self-healing hydrophilic coating raw materials: Polyvinyl alcohol (manufacturer: Kuraray, model: PVA-224, alcoholysis degree 87%-89%, molecular weight 88,000-98,000); Polyurethane elastomer (manufacturer: Bayer, model: Desmopan® TPU 9370A); Thermosensitive polymer (poly (N-isopropylacrylamide), manufacturer: Sigma-Aldrich, model: P4257); Nanomaterials (nano titanium dioxide, manufacturer: Evonik, Germany, model: P25); Solvent for solvation modification (isopropanol, manufacturer: Shanghai McLean Biochemical Technology Co., Ltd., model: AR grade)
[0059] Equipment: Plate and frame membrane preparation machine, film coating machine, vacuum drying oven, high pressure reactor.
[0060] Preparation steps S1: Preparation of base membrane: Directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, with a base membrane thickness of 200 microns, for subsequent coating process.
[0061] S2: Preparation of self-healing hydrophilic coating: Add polyvinyl alcohol (80 parts) and polyurethane elastomer (120 parts) into isopropanol (70 parts), stir evenly to form a mixed solution; Thermosensitive polymer (10 parts) and nano-titanium dioxide (5 parts) were added to the mixed solution, and stirring was continued for 2 hours to obtain a uniformly dispersed coating precursor solution.
[0062] S3: Solvation modification treatment: The coating precursor liquid was placed in a high-pressure reactor and subjected to a solvent modification treatment at 250° C. and 1 MPa for 2 hours to prepare a coating material with excellent hydrophilicity.
[0063] S4: coating process: Use a coating machine to evenly coat the prepared self-healing hydrophilic coating on the surface of the base film to ensure that there are no bubbles and coating defects; the coating thickness is controlled to be 15 microns.
[0064] S5: Curing process: The coated film was placed in a vacuum drying oven and dried at 80° C. for 6 hours to completely cure the coating to obtain the final plate-and-frame film.
[0065] Example 4 The difference from Example 1 is that the nano titanium dioxide is functionalized.
[0066] Materials required for the preparation of functionalized nano-titanium dioxide: Nano titanium dioxide powder (manufacturer: Evonik, Germany, model: P25); Anhydrous ethanol (manufacturer: Sinopharm Chemical Reagent Co., Ltd., model: AR grade); Aminotrichlorosilane (Manufacturer: Sigma-Aldrich, Model: 440159).
[0067] The preparation steps of functionalized nano-titanium dioxide are as follows: Step 1: Dissolve nano-titanium dioxide powder (50 g) in 500 mL of anhydrous ethanol and use an ultrasonic device to shake for 30 minutes to remove impurities; wash the nano-titanium dioxide with deionized water until the pH value of the washing solution is close to neutral; Step 2: Dry the washed nano-titanium dioxide at 70° C. for 12 hours to obtain a dry powder; Step 3: Evenly mix anhydrous ethanol, deionized water and aminotrichlorosilane in a mass ratio of 1:1:0.1; wherein the mass of aminotrichlorosilane is 1 / 10 of the nano titanium dioxide powder; Step 4: adding dried nano-titanium dioxide to the reaction solution, stirring and reacting at 25° C. for 4 hours to form functionalized nano-titanium dioxide; Step 5: Separate the reaction product by centrifugation, and repeatedly wash it with anhydrous ethanol and deionized water; dry the washed nano-titanium dioxide at 60° C. for 12 hours to obtain surface functionalized nano-titanium dioxide.
[0068] Example 5 The difference from Example 4 is that a conductive polymer material (polyaniline, manufacturer: Jiangsu Huakai New Materials Co., Ltd., model: PANI-HS) is also added to the raw material of the self-healing hydrophilic coating.
[0069] The preparation steps are as follows: S1: Preparation of base membrane: Directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, with a base membrane thickness of 150 μm, for subsequent coating process.
[0070] S2: Preparation of self-healing hydrophilic coating: Add polyvinyl alcohol (70 parts) and polyurethane elastomer (110 parts) into isopropanol (50 parts), stir evenly to form a mixed solution; Thermosensitive polymer (8 parts), functionalized nano-titanium dioxide (3 parts), and conductive polymer material (2 parts) were added to the mixed solution, and stirring was continued for 2 hours to obtain a uniformly dispersed coating precursor solution.
[0071] S3: Solvation modification treatment: The coating precursor liquid was placed in a high-pressure reactor and subjected to a solvent modification treatment at 200° C. and 1 MPa for 3 hours to prepare a coating material with excellent hydrophilicity.
[0072] S4: coating process: Use a coating machine to evenly coat the prepared self-healing hydrophilic coating on the surface of the base film to ensure that there are no bubbles and coating defects; the coating thickness is controlled to be 12 microns.
[0073] S5: Curing process: The coated film was placed in a vacuum drying oven and dried at 80° C. for 6 hours to completely cure the coating to obtain the final plate-and-frame film.
[0074] Example 6 The difference from Example 5 is that metal nanoparticles (nanosilver, manufacturer: Sigma-Aldrich Company, USA, model: 720002) are also added to the raw material of the self-healing hydrophilic coating.
[0075] The preparation steps are as follows: S1: Preparation of base membrane: Directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, with a base membrane thickness of 150 μm, for subsequent coating process.
[0076] S2: Preparation of self-healing hydrophilic coating: Add polyvinyl alcohol (70 parts) and polyurethane elastomer (110 parts) into isopropanol (50 parts), stir evenly to form a mixed solution; Add the thermosensitive polymer (8 parts), functionalized nano titanium dioxide (3 parts), conductive polymer material (2 parts) and nano silver particles (1 part) to the mixed solution, and continue stirring for 2 hours to obtain a uniformly dispersed coating precursor solution.
[0077] S3: Solvation modification treatment: The coating precursor liquid was placed in a high-pressure reactor and subjected to a solvent modification treatment at 200° C. and 1 MPa for 3 hours to prepare a coating material with excellent hydrophilicity.
[0078] S4: coating process: Use a coating machine to evenly coat the prepared self-healing hydrophilic coating on the surface of the base film to ensure that there are no bubbles and coating defects; the coating thickness is controlled to be 12 microns.
[0079] Comparative Example 1 is to directly purchase UE010MF polyethersulfone ultrafiltration membrane produced by Pall Corporation of the United States, and the base membrane thickness is 200 microns.
[0080] Detection Methods The film samples of Examples 1 to 6 and Comparative Example 1 and a polypropylene mesh support substrate (mesh size 20 μm, thickness 200 μm) were stacked and assembled into a plate-frame mold, and the following tests were performed. The test results are shown in Table 1: 1. Flux test: use deionized water, temperature 25℃, pressure 0.4MPa, membrane area 0.1m², test time 1 hour. The basic flux is usually calculated by the following formula: Is the basic flux, usually in L·m -2 ·h -1 .
[0081] V is the volume of liquid that passes through the membrane, and its unit is L (liter).
[0082] A is the effective area of the membrane, in m² (square meters).
[0083] Δt is the experimental time, the unit is h (hour).
[0084] Table 1 2. Continuous flux decay test: 2.1. Pollution test 2.1.1 Conditions: 1) Sewage composition: simulated printing and dyeing wastewater, including 50mg / L of active red dye, 30mg / L of active blue dye, 200mg / L of suspended solids, 50mg / L of oil and fat, and chromium ion (Cr 2+ ) concentration 1mg / L, copper ion (Cu 2+ ) concentration 0.5mg / L, nickel ion (Ni 2+ ) concentration 0.3mg / L, sodium chloride 1000mg / L, sodium sulfate 500mg / L.
[0085] 2) Operating pressure: 0.2MPa 3) Temperature: 25℃ 4) Filtration time: 10 hours 2.1.2 Calculate the flux decay rate of the membrane: is the initial basic flux (L·m -2 ·h -1 ), is the membrane flux during filtration (L·m -2 ·h -1 ).
[0086] If the flux attenuation exceeds 20%, it means that the membrane's anti-pollution ability is poor.
[0087] 2.2 Cleaning recovery test 2.2.1 Conditions: 1) Cleaning solution: 0.5M sodium hydroxide solution (used to remove organic pollutants) 2) Cleaning time: 2 hours 3) Post-cleaning operation: pure water permeation 2.2.2 Data Recording: Flux comparison before and after cleaning: Record the flux after cleaning and calculate the cleaning recovery rate: is the membrane flux after cleaning (L·m -2 ·h -1 ), is the initial basic flux (L·m -2 ·h -1 ).
[0088] The test results are shown in Table 2: Table 2 The above flux units are (L·m -2 ·h -1 ).
[0089] The flux of Comparative Example 1 decreases rapidly (>30%) because it has no coating protection and poor anti-pollution performance. Examples 1-6 have different degrees of self-repairing hydrophilic coatings and functional materials (such as functionalized nanomaterials, conductive polymer materials, and nanosilver), and their flux decreases relatively slowly, especially Example 6, which has the smallest decrease.
[0090] The above is only a preferred embodiment of the present invention, and the protection scope of the present invention is not limited to the above embodiments. All technical solutions under the concept of the present invention belong to the protection scope of the present invention. It should be pointed out that for ordinary technicians in this technical field, some improvements and modifications without departing from the principle of the present invention should also be regarded as the protection scope of the present invention.
Claims
1. A plate-and-frame membrane for treating printing and dyeing wastewater, characterized in that: It comprises a base film and a self-repairing hydrophilic coating coated on the surface of the base film, wherein: The base membrane is a polyethersulfone ultrafiltration membrane, which is made of polyethersulfone polymer material; The self-repairing hydrophilic coating is prepared by comprising the following components in parts by weight: 60-80 parts of polyvinyl alcohol; 100-120 parts of polyurethane elastomer; 5 to 10 parts of a thermosensitive polymer; 2-5 parts of nanomaterials; 20 to 70 parts of solvent for solvation modification; Wherein, the temperature-sensitive polymer is selected from one of poly (N-isopropylacrylamide) or poly (vinyl alcohol)-poly (N-isopropylacrylamide) copolymer; The nano material is selected from one of nano titanium dioxide or graphene oxide; The solvent for solvation modification is selected from one or more of alcohol solvents, ketone solvents or ether solvents; The solvation modification conditions are a temperature of 150° C. to 250° C. and a pressure of 0.5 MPa to 2 MPa.
2. A plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The nano material is nano titanium dioxide with surface functionalization treatment, and the surface functionalization treatment steps are as follows: Step 1: Dissolve nano-titanium dioxide powder in anhydrous ethanol, ultrasonically vibrate to remove impurities, and wash with deionized water until the pH value is close to neutral; Step 2: Dry the washed nano titanium dioxide at 60-80°C for 12 hours; Step 3: Mixing anhydrous ethanol, deionized water and aminotrichlorosilane to obtain a reaction solution, wherein the mass of the aminotrichlorosilane is 1 / 10 of the nano titanium dioxide powder; Step 4: adding the dried nano titanium dioxide to the reaction solution, stirring and reacting at 25° C. for 2 to 6 hours to form functionalized nano titanium dioxide; Step 5: Wash the reaction product by centrifugation or filtration, and repeatedly wash with anhydrous ethanol and deionized water to remove unreacted reagents and by-products; Step 6: Dry the cleaned nano-titanium dioxide at 60° C. for 12 hours to obtain surface functionalized nano-titanium dioxide.
3. A plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The invention also comprises 1 to 3 parts by weight of a conductive polymer material, wherein the conductive polymer material is selected from polyaniline or polypyrrole.
4. A plate-and-frame membrane for treating printing and dyeing wastewater according to claim 3, characterized in that: The invention also comprises 0.5 to 2 parts by weight of metal nanoparticles, wherein the metal nanoparticles are nanosilver.
5. The plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The thickness of the base film is 100 to 200 microns.
6. The plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The thickness of the self-repairing hydrophilic coating is 10 to 15 microns.
7. The plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The alcohol solvent used in the solvation modification is one of methanol, ethanol and isopropanol, the ketone solvent is one of acetone and dimethyl ketone, and the ether solvent is one of dimethyl ether and tetrahydrofuran.
8. The plate-and-frame membrane for treating printing and dyeing wastewater according to claim 1, characterized in that: The amount of hydrophilic functional groups introduced into the coating is 0.5-2 mmol / g.
9. A method for preparing a plate-and-frame membrane for treating printing and dyeing wastewater according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1: preparing a base membrane, wherein the base membrane is a polyethersulfone ultrafiltration membrane made of a polyethersulfone polymer material; S2: preparing a self-healing hydrophilic coating, mixing polyvinyl alcohol, polyurethane elastomer, thermosensitive polymer and solvent for solvation modification, and then adding nanomaterials; Wherein, the temperature-sensitive polymer is selected from poly (N-isopropylacrylamide) or poly (vinyl alcohol)-poly (N-isopropylacrylamide) copolymer, and the nanomaterial is selected from nano titanium dioxide or graphene oxide; S3: performing a solvation modification treatment, the specific method being: performing a solvation modification under the conditions of a temperature of 150° C. to 250° C. and a pressure of 0.5 MPa to 2 MPa; S4: coating the self-healing hydrophilic coating on the surface of the base film, ensuring that the coating is uniform and free of bubbles; S5: The coating is solidified by drying or hot pressing to obtain a plate-and-frame membrane for treating printing and dyeing wastewater.
10. The method for preparing a plate-and-frame membrane for treating printing and dyeing wastewater according to claim 9, characterized in that: In the solvation modification process of step S3, the alcohol solvent used is one of methanol, ethanol or isopropanol, the ketone solvent used is one of acetone or dimethyl ketone, and the ether solvent used is one of dimethyl ether or tetrahydrofuran.
Citation Information
Patent Citations
Preparation method of ammonolysis oxidized graphene-based 3D (Three-dimensional) nanoparticle modified organic separation membrane
CN106582299A
Nanofiltration membrane for one-piece intelligent water purification faucet and preparation method thereof
CN106621836A
Antibacterial conductive composite film for water treatment as well as preparation method and application of antibacterial conductive composite film
CN114699931A
Temperature-responsive membrane, temperature-responsive membrane module, and membrane filtration system in which the same are used
CN1962040A